The Home Care Home – An Un-Total Institution. When the Care Home Logic Permeates the Private Space - Möllergren, Glenn (Socialinė teorija, empirija, politika ir praktika, 2024)
This article examines how the provision of home care services impact older individuals in Sweden, focusing on how it may subtly institutionalise their daily lives. Domiciliary care is found to negatively impact users’ individuality and independence, contrary to initial intentions of offering an emancipatory alternative to nursing facilities.The study uses Goffman’s concept of total institutions, operationalised by identifying aspects of everyday life within which institutionalisation manifests itself, including meals, daily rhythmics, and lifestyle choices.For this article, the experiences of home care users in Sweden were collected in 34 qualitative interviews and 15 observations with respondents aged between 68 and 96 years. The material was examined using theory-driven thematic analysis.Results show that while some care users find comfort in the structures imposed to their lives, many are faced with limitations related to the tight, minute-timed scheduling and the assembly-line style of care provision. The constraints affect everyday life choices related to eating, sleeping hours, hobbies, and the sense of home, which are all influenced by the care organisation’s work regime and scheduling.The analysis concludes by proposing the term “home care home”. This designation indicates the challenges to individuality entailed in the home care rationale, while acknowledging that the influence on users is “less-than-total”, as compared to typical institutionalising environments such as prisons or hospitals.While a total institution is commonly understood as a spatial structure, it also functions as a logic acting regardless of physical constraints – for instance, in a person’s home. Moreover, the study suggests that this logic may be at work anywhere within large-scale production of human services.In summary, this article addresses the individuality-eroding force ingrained in home care provision and emphasises the need to strengthen users’ influence on care provision in order to increase their independence.